PENGARUH INDIKATOR RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS DAN CAPITAL (RGEC) TERHADAP INTERNET FINANCIAL REPORTING (Studi Empiris pada Emiten Bank di Indonesia Periode 2008-2018) - Dwi Puspita Agustin; Lana Sularto (Institut Bisnis Muhammadiyah Bekasi, 2021)
Management is used to convey information to external parties of the company through financial reporting, through the internet network. Internet Financial Reporting is the disclosure of financial statements made by companies using internet media, disclosure of these financial statements can be in the form of reports submitted on the company's website or financial statements published on the stock exchange. The purpose of this study is to see the effect of bank soundness with Risk Profile, Good Corporate Governance, Earnings and Capital (RGEC) indicators on Internet Financial Reporting Empirical Studies on Issuer Banks in Indonesia in the financial reporting period from 2008 to 2018. Methods sampling in this study using certain characteristics contained in the sample (purposive sampling) and the test tool used for analysis is multiple linear regression as a test tool using SPSS 25.0. The sample in this study were 10 companies with a research period of 11 years. The results of this study indicate that only the ROE and CAR ratios affect Internet Financial Reporting (IFR), while for NPL, LDR, GCG, and NIM, whether good or bad, the calculations do not affect Internet Financial Reporting or disclosures made by companies in each bank.